Implementasi Teknologi Informasi Untuk Meningkatkan Aksesibilitas Dan Konektivitas Di Nagari Pasilihan - Muhammad Nasir; Ulfa Nur Azizah; Riyan Afandi; Yoga Alfikri; Nia Ramadhani; Linda Rosalina (CV. ITTC INDONESIA, 2025)
This study aims to analyze the accessibility and connectivity conditions of information technology in Nagari Pasilihan, a remote area facing various challenges related to technological infrastructure. Using a qualitative approach with a descriptive method, this research explores the perceptions of the community, technology managers, and local policymakers regarding the obstacles they face in accessing information technology and the solutions that can be implemented to improve accessibility. The findings show that the majority of the population in Nagari Pasilihan experiences difficulties in accessing the internet due to poor network quality, high costs, and low levels of digital literacy. Although most of the population uses information technology daily, they are still limited by inadequate infrastructure. The recommendations proposed include improving network infrastructure, reducing internet access costs, and providing digital literacy training. This study also emphasizes the importance of collaboration between the government, the private sector, and the community in enhancing connectivity and accessibility in remote areas.